1999
DOI: 10.1164/ajrccm.160.4.9810071
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Chronic Lung Disease in Extremely Immature Baboons

Abstract: A borderline viability model of bronchopulmonary dysplasia (BPD)/chronic lung disease of infancy (CLD) with pathophysiologic parameters consistent with those in extremely immature humans with BPD/CLD is described. After prenatal steroid treatment of pregnant dams, 12 premature baboons were delivered by cesarean-section at 125 d (term gestation, 185 d), treated with exogenous surfactant, and maintained on appropriate oxygen and positive pressure ventilation for at least 1 to 2 mo. In spite of appropriate oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

25
422
3
19

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 464 publications
(474 citation statements)
references
References 47 publications
25
422
3
19
Order By: Relevance
“…The consensus from these histologic studies is that there is delay in acinar and alveolar development in preterm survivors up to 3 years of age. Taken together with the theory that human alveolarization is complete at 3 years, it was assumed that deranged alveolar structure would be a lifelong feature in preterm survivors (9,15).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The consensus from these histologic studies is that there is delay in acinar and alveolar development in preterm survivors up to 3 years of age. Taken together with the theory that human alveolarization is complete at 3 years, it was assumed that deranged alveolar structure would be a lifelong feature in preterm survivors (9,15).…”
Section: Discussionmentioning
confidence: 99%
“…The preterm baboon model of CLD was designed to resolve this problem. It (9,36) showed that alveolar hypoplasia was the predominant feature of "new CLD" (use of prenatal steroids and postnatal surfactant combined with "gentle ventilation"). Despite this pioneering work, there were no data on long-term survivors, because the maximum survival reported is 8 months, a human developmental equivalent of 3 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously determined whether there are alterations in NOS in proximal lung and accompanying changes in NO production in a model of BPD in baboon fetuses delivered at 125 days of gestation (term 5 185 d) and ventilated for 14 days. This model best exemplifies the current form of BPD observed in extremely preterm human infants (11). In contrast to the normal 73% increase in NOS activity AT A GLANCE COMMENTARY Scientific Knowledge on the Subject Postnatal therapies to prevent bronchopulmonary dysplasia (BPD) in preterm infants are limited.…”
mentioning
confidence: 86%